The Price of Female Headship: Gender, Inheritance and Wealth Accumulation in the United States - Conley, Dalton; Ryvicker, Miriam (Journal of Income Distribution®, 2005)
Female-headed households in the United States suffer from lower levels of asset ownership than their male-headed counterparts. This gap remains after controlling for the lower incomes of female heads. What, then, produces the gender discrepancy in net worth? Using longitudinal, intergenerational data from the Panel Study of Income Dynamics, we ask whether differential patterns of inheritance, savings rates or investment yield this female-male asset gap. Results demonstrate that differential savings rates between female- and male-headed households account for the gender gap in net worth. We speculate on the financial constraints within female-headed households that account for the savings rate differential.